مشهد الوداع في الشعر العربي الحديث ما بين الْأَصالة والتجديد/ Farewell Scene in modern Arabic Poetry: Originality of Innovation? - Azzain, Muhammad Musa Al-Balulah (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2019)
ملخص البحث: تهدف الدراسة إلى إبراز هذا الجانب الإنساني، والتأسيس له ليصبح معنىً شعرياً يُـضَاف إلى أبواب الشعر ومعانيه، فضلاً عن إعادة الرؤية إلى معاني الشعر من منظور معاصر لا ينفصل عن سياقه التقليدي. أما خطة هذه الدراسة فجاءت في مقدمة وثلاثة مباحث وخاتمة، اتَّبعنا فيها المنهج الوصفي التحليلي، ولما كان الموضوع أكثر ارتباطاً بالجانب الذاتي، استخدمنا التحليل النفسي بالقدر الذي يتحمله النص؛ حتى لا تخرج الدراسة عن إطارها الأدبي. وفي الخاتمة تناولنا خطة البحث تناولاً مبسطاً، وذكرنا أبرز النتائج التي توصل إليها وهي: إن مشهد الوداع قد تطور وفقاً للتطورات التي عاشها الإنسان العربي في كل عصر، وإن لمشهد الوداع في الشعر العربي صورة نفسية شديدة الأثر وعميقة الإحساس، يسودها الحزن والقلق والخوف والارتباك والتشاؤم، وإن مشهد وداع الشاعر لموطنه وأهله ومَن يحب، يؤكد قوة ارتباطه الوجداني بالمكان الذي نشأ فيه والمجتمع الذي عاش وترعرع فيه وسط أهله وأقرانه وأصحابه، وإن مشهد الوداع في العصور الأولى يأتي في أغلب القصائد الشعرية عرضاً ومندساً في أغراض الشعر المتعارف عليها وفي أبيات قليلة، ونادراً ما يأتي قصيدة كاملة، يحمل عنوانها اسم الوداع أو معناه، وفي العصر الحديث تكثر قصائد مشهد الكلمات المفتاحية: مشهد-الوداع-الشعر-الحديث-الأصالة-التجديد. Abstract The study aims to point out this human side and establish its poetic meaning that would be added to the topics of the Arabic poetry and its meanings. This is in addition to reviewing the meanings of the Arabic poetry from a modern perspective that is within its traditional context. The study consists of an introduction, three chapters, and a conclusion. The researcher uses a descriptive analytical approach. Whereas the subject of the study is more closely related to the personal side, the researcher uses the psychoanalysis method in as much as it is compatible with the text so that it does not go beyond the intended literary framework. In the conclusion, the researcher dealt with the research plan in a simple way, and he highlighted the findings as follows: The farewell scene has evolved according to the developments experienced by the Arab in every epoch; the farewell scene has a psychological image that has a severe impression on both parties found in sadness, anxiety, fear, confusion, and pessimism at the moment of the farewell; the poet’s home, town or village farewell statement confirms the strong sentimental attachment and nostalgia to the place where he grew up among his peers, relatives and friends. It has a spiritual bond and precious memory that will inflict suffering when parting with them; despite the inevitability and necessity of separation in the same time but with supplication and hopefulness, there was hope to return and pledge to keep cordiality, brings about the love of life and longing for it’s reasons in both parties; the farewell scene in ancient times comes inessential and hidden in the well-known poetry purposes and in few verses, but in the sequential states’ epoch (an era of degradation), and the Renaissance comes independent as a complete poem entitled (the farewell); the farewell poetry in all epochs has formed a phenomenon that aroused attention. This needs a critical vision that can set up for this human purpose and adds a new meaning to this already established genre in the Arabic literature. Keywords: Scenery – Farewell – Poetry – Modernity – Originality – Renewal Abstrak Kajian ini adalah bertujuan untuk menyerlahkan aspek kemanusiaan ini dan merumuskan maksud puisi yang dapat ditambahkan lagi kepada maksud puisi Arab. Ini disamping melihat kembali maksud puisi Arab itu sendiri daripada perspektif moden namun dalam rangka tradisionalnya. Kajian ini mengandungi pendahuluan, tiga bahagian dan satu kesimpulan. Pengkaji menggunakan pendekatan deskriptif dan analitik. Memandangkan topik kajian adalah lebih dekat kepada aspek peribadi, pengkaji menggunakan metod psikoanalisis selagi mana ia sesuai dengan teks untuk ia tidak menjangkau kerangka kesusasteraannya. Kesimpulan kajian adalah seperti berikut: babak mengucap selamat tinggal telah berubah mengikut perkembangan yagn dialami oleh bangsa Arab pada setiap era; babak ini mempunyai gambaran psikologi yang mempunyai kesan mendalam kepada kedua-dua pihak yang mencetuskan kesedihan, kebimbangan, ketakutan, kekeliruan dan buruk sangka pada waktu perpisahan itu berlaku. Tempat asal penyair, pekan atau kempungnya yang termaktud dalam pernyataan perpisahan itu mengesahkan lagi kuatnya pautan sentimental serta nostalgia kepada tempat beliau membesar bersama sanak saudara dan rakan-rakannya. Ia mempunyai hubungan rohani dan memori yang berharga yang akan mencetuskan penderitaan apabila berpisah dengannya; walaupun kepastian dan keperluan perpisahan itu namun dengan harapan serta doa, masih ada lagi sekelumit harapan untuk kembali dan janji untuk memelihara hubungan karib, ini membawa kepada lahirnya cinta dan harapan untuk meneruskan kehidupan oleh kedua-dua pihak; babak selamat tinggal pada waktu silam tersirat dalam tema puisi yang mempunyai tujuan lain yagn pelbagai namun sewaktu era kejatuhan dan kebangkitan tema ini menjadi tersendiri dan membentuk tajuknya yang tersendiri. Puisi selamat tinggal dalam semua era telah mencetuskan fenomena yang menarik perhatian. Ini memerlukan satu kupasan yang kritikal yang dapat memudahkan aspek kemanusiaan ini dan menambah satu maksud baharu dalam kesusasteraan Arab. Kata kunci: Babak – Selamat tinggal – Puisi – Kemodenan – Keaslian – Pembaharuan.